2013
DOI: 10.1186/1742-2094-10-102
|View full text |Cite
|
Sign up to set email alerts
|

Western-type diet modulates inflammatory responses and impairs functional outcome following permanent middle cerebral artery occlusion in aged mice expressing the human apolipoprotein E4 allele

Abstract: BackgroundNumerous clinical trials in stroke have failed, most probably partially due to preclinical studies using young, healthy male rodents with little relevance to the heterogenic conditions of human stroke. Co-morbid conditions such as atherosclerosis and infections coupled with advanced age are known to contribute to increased risk of cerebrovascular diseases. Clinical and preclinical studies have shown that the E4 allele of human apolipoprotein (ApoE4) is linked to poorer outcome in various conditions o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 48 publications
2
25
0
Order By: Relevance
“…Therefore, reducing inflammatory responses in the ischemic brain tissues might be a mechanism for TSC‐induced neuroprotection. Consistent with this possibility, enhancing neuroinflammation after brain ischemia might contribute to the worsened neurological outcome in rodents with obesity (Tu et al, ; Dhungana et al, )…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Therefore, reducing inflammatory responses in the ischemic brain tissues might be a mechanism for TSC‐induced neuroprotection. Consistent with this possibility, enhancing neuroinflammation after brain ischemia might contribute to the worsened neurological outcome in rodents with obesity (Tu et al, ; Dhungana et al, )…”
Section: Discussionmentioning
confidence: 84%
“…Hyperlipidemia has also been shown to increase stroke severity (Mikdashi et al, 2007), although opposite findings have been reported (Olsen et al, 2007;Jimenez-Conde et al, 2010). Obesity can induce neuroinflammation (Purkayastha and Cai, 2013;Buckman et al, 2014) and worsen neuroinflammation and neurological outcomes after brain ischemia (Tu et al, 2011;Dhungana et al, 2013). Neuroinflammation is a significant pathological process that leads to cell injury (Lipton, 1999;Li et al, 2013).…”
mentioning
confidence: 99%
“…The temperature of the mice was controlled by a homeothermic control system connected to a heating blanket and rectal probe (Harvard apparatus; PanLab, Barcelona, Spain). The left middle cerebral artery (MCA) was permanently occluded as described (Dhungana et al, 2013b). Briefly, the temporal bone was first exposed and a 1-mm-diameter hole was drilled to expose the artery.…”
Section: Ischemia Surgerymentioning
confidence: 99%
“…Nonetheless, how apoE status affects obesity-associated inflammation is unclear, as one study reported that apoE knockout mice show a stronger pro-inflammatory response in adipose tissue than wildtype mice (Pereira et al, 2012), whereas another study found that apoE knockout mice on HFD have lower levels of inflammatory cytokines in adipose tissue and skeletal muscle (Wang et al, 2012). Interestingly, apoE4 mice fed a HFD are more susceptible to motor deficits after stroke, and this is accompanied by increased inflammation (Dhungana et al, 2013). Overall, the literature demonstrates an interaction between apoE and obesity, but more research is needed to clarify how this relationship affects inflammation.…”
Section: Mechanisms Underlying Sex Differences In Obesity and Alzhmentioning
confidence: 99%